Comparative Efficacy and Safety of Self-Expanding Versus Balloon-Expandable TAVR in Patients with Aortic Stenosis: A Systematic Review and Meta-Analysis - Warda Zaheer, Manahil Asghar (Students' Supplement of Journal of Rawalpindi Medical College, 2025)
Introduction: Patients with aortic stenosis have a high mortality risk. New self-expanding valves (SEV) and balloon expandable valves (BEV) are used in trans catheter aortic valve replacement (TAVR). We performed a systematic review and meta-analysis to compare the clinical outcomes of efficacy and safety of these two valves in patients with aortic stenosis. Methods: A systematic search of PubMed, Embase, and Cochrane was conducted from inception to June 2024. Randomized controlled trials that included adult human patients with aortic stenosis undergoing TAVR, comparing clinical outcomes of efficacy and safety between SEV and BEV, were eligible. Random effects meta-analysis using the inverse variance method was employed. Quality appraisal was done using the Cochrane Risk of Bias 2 Tool. This review was registered with PROSPERO, CRD42024563628. Results: We identified 8 RCTs, and data from 2779 patients were analyzed. Random effects analysis showed that SEV, when compared to BEV, significantly increased risk of all-cause mortality RR = 1.84, 95% CI: 1.11-3.04), cardiovascular mortality RR 2.00 (95% CI: 1.05-3.83), and permanent pacemaker implantation RR = 1.67 (95% CI: 1.22-2.28) at 30 days. However, these outcomes were not statistically significant for 1 year. Other assessed outcomes, like stroke, acute kidney injury, and myocardial infarction, also did not have statistically significant results. Conclusion: BEV had improved mortality outcomes compared to SEV in the short term. However, future clinical trials with larger sample sizes are needed for a comprehensive understanding. Keywords: transcatheter aortic valve replacement; self-expanding valve; balloon expandable valve; aortic stenosis; meta-analysis